The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/clockssleep2020014
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Visual vs. Acoustic Closed-Loop Stimulation on EEG Power Density during NREM Sleep in Humans

Abstract: The aim of the study was to investigate whether visual stimuli have the same potency to increase electroencephalography (EEG) delta wave power density during non-rapid eye movement (NREM) sleep as do auditory stimuli that may be practical in the treatment of some sleep disturbances. Nine healthy subjects underwent two polysomnography sessions—adaptation and experimental—with EEG electrodes positioned at Fz–Cz. Individually adjusted auditory (pink noise) and visual (light-emitting diode (LED) red light) paired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Although how exactly sleep influences memory is a matter of debate (Ellenbogen et al, 2006), consolidation of both declarative and procedural memory is a well‐established target of SWA (Born et al, 2006), and potentiation of memory in human subjects has been observed after transcranial application of electrical or magnetic oscillating potentials (Marshall et al, 2006) as well as after CLAS (see above) and occasionally closed loop visual, olfactory, and somatosensory stimulation (Bellesi et al, 2014; Choi et al, 2020; Danilenko et al, 2020; Riedner et al, 2011). To date, our recognition of the importance of sleep for performance in learning and memory tasks has relied on studies based on sleep deprivation/restriction (Alkadhi et al, 2013; Colavito et al, 2013), while noninvasive brain stimulation allows the investigation of memory function using detailed perturbation of sleep stages (Harrington & Cairney, 2021).…”
Section: Induction or Enhancement Of Sleep Swa By Noninvasive Brain S...mentioning
confidence: 99%
“…Although how exactly sleep influences memory is a matter of debate (Ellenbogen et al, 2006), consolidation of both declarative and procedural memory is a well‐established target of SWA (Born et al, 2006), and potentiation of memory in human subjects has been observed after transcranial application of electrical or magnetic oscillating potentials (Marshall et al, 2006) as well as after CLAS (see above) and occasionally closed loop visual, olfactory, and somatosensory stimulation (Bellesi et al, 2014; Choi et al, 2020; Danilenko et al, 2020; Riedner et al, 2011). To date, our recognition of the importance of sleep for performance in learning and memory tasks has relied on studies based on sleep deprivation/restriction (Alkadhi et al, 2013; Colavito et al, 2013), while noninvasive brain stimulation allows the investigation of memory function using detailed perturbation of sleep stages (Harrington & Cairney, 2021).…”
Section: Induction or Enhancement Of Sleep Swa By Noninvasive Brain S...mentioning
confidence: 99%
“…Previous studies indicate that rhythmic vestibular stimulation may also increase slow frequency activity and deepen sleep during a daytime nap (Bayer et al, 2011 ). On the other hand, repetitive visual stimulation was not effective to enhance slow wave activity in contrast to acoustic stimulation of similar rhythmicity (Danilenko et al, 2020 ). The sleeping brain is particularly sensitive to information arising from the body (Wei & Van Someren, 2020 ), therefore, slow waves might be effectively elicited through the somatosensory pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The electroencephalography (EEG) is most used for its examination [ 3 ]. Four sleep stages are commonly detected according to the more recent guidelines published by the American Academy of Sleep Medicine (AASM) [ 4 ]: three non-rapid eye movement stages (NREM1, NREM2, and NREM3) and rapid eye movement (REM) sleep [ 5 , 6 ]. Deep sleep (NREM3) plays an important role in memory consolidation.…”
Section: Introductionmentioning
confidence: 99%